What if Virtual Reality could be used as a Tool in Positive Psychotherapy in Brazil? - Kunst, Marina Holanda; Teixeira, João Marcelo Xavier Natário; Peres, Fabiana F. F.; Mauricio, Claudio R. M. (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2024)
Virtual Reality allows the user to experience a sense of presence and immersion in a three-dimensional virtual environment. Such sense is provided by tracking head movement, that naturally changes the virtual images and motion. VR can be used as a tool in clinical psychology, being its incorporation by psychologists advantageous. Thus, the effectiveness of psychotherapy integrated with VR for the treatment of psychological disorders has been shown in some studies. However, to ensure the appropriate use of VR, psychologists must have a clear understanding of the opportunities and challenges this tool may provide in professional practice. This article describes the first steps in incorporating VR into psychotherapy procedures in Brazil. In particular, the paper focuses on the validation of the developed virtual environments by psychologists, the introduction of narratives, and the prospects to implement VR in psychotherapy to improve the well-being of patients.